Cell‐instructive biomaterials in tissue engineering and regenerative medicine. Issue 5 (13th February 2023) - Adhikari, Bikram; Stager, Michael A.; Krebs, Melissa D.
Abstract: The field of biomaterials aims to improve regenerative outcomes or scientific understanding for a wide range of tissue types and ailments. Biomaterials can be fabricated from natural or synthetic sources and display a plethora of mechanical, electrical, and geometrical properties dependent on their desired application. To date, most biomaterial systems designed for eventual translation to the clinic rely on soluble signaling moieties, such as growth factors, to elicit a specific cellular response. However, these soluble factors are often limited by high cost, convoluted synthesis, low stability, and difficulty in regulation, making the translation of these biomaterials systems to clinical or commercial applications a long and arduous process. In response to this, significant effort has been dedicated to researching cell‐directive biomaterials which can signal for specific cell behavior in the absence of soluble factors. Cells of all tissue types have been shown to be innately in tune with their microenvironment, which is a biological phenomenon that can be exploited by researchers to design materials that direct cell behavior based on their intrinsic characteristics. This review will focus on recent developments in biomaterials that direct cell behavior using biomaterial properties such as charge, peptide presentation, and micro‐ or nano‐geometry. These next generation biomaterials could offer significant strides in the development of clinically relevant medical devices which improve our understanding of the cellular microenvironment and enhance patient care in a variety of ailments.